2017
DOI: 10.1371/journal.pone.0169953
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Can Influence Mitochondrial Inheritance in the Saccharomyces Yeast Hybrids

Abstract: Mitochondria play a critical role in the generation of metabolic energy and are crucial for eukaryotic cell survival and proliferation. In most sexual eukaryotes, mitochondrial DNA (mtDNA) is inherited from only one parent in non-Mendelian inheritance in contrast to the inheritance of nuclear DNA. The model organism Saccharomyces cerevisiae is commonly used to study mitochondrial biology. It has two mating types: MATa and MATα. Previous studies have suggested that the mtDNA inheritance patterns in hybrid diplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
(46 reference statements)
1
13
0
Order By: Relevance
“…in warm glucose-based media) to construct crosses, rather than a respiratory media, on which we almost exclusively observed S. cerevisiae mtDNA inheritance. There may be a strong strain dependence of mtDNA inheritance, a phenomenon also suggested by other groups (Solieri et al 2008;Albertin et al 2013) and supported by a recent study of mtDNA inheritance in crosses of S. cerevisiae and Saccharomyces paradoxus where both YPD and YP + glycerol were used as carbon source (Hsu and Chou 2017). Here they found that crossing one pair of S. cerevisiae and S. paradoxus strains in YPD (with 2 % glucose, as with our study) and YP + glycerol resulted in the retention of mtDNA from the S. cerevisiae parent, whilst crossing an alternative pair (different strains) of S. cerevisiae and S. paradoxus) resulted in the retention of mtDNA from the S. paradoxus parent, regardless of carbon source.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…in warm glucose-based media) to construct crosses, rather than a respiratory media, on which we almost exclusively observed S. cerevisiae mtDNA inheritance. There may be a strong strain dependence of mtDNA inheritance, a phenomenon also suggested by other groups (Solieri et al 2008;Albertin et al 2013) and supported by a recent study of mtDNA inheritance in crosses of S. cerevisiae and Saccharomyces paradoxus where both YPD and YP + glycerol were used as carbon source (Hsu and Chou 2017). Here they found that crossing one pair of S. cerevisiae and S. paradoxus strains in YPD (with 2 % glucose, as with our study) and YP + glycerol resulted in the retention of mtDNA from the S. cerevisiae parent, whilst crossing an alternative pair (different strains) of S. cerevisiae and S. paradoxus) resulted in the retention of mtDNA from the S. paradoxus parent, regardless of carbon source.…”
Section: Discussionsupporting
confidence: 56%
“…For example, S. cerevisiae has eight origins of replication whilst S. uvarum has four (Masneuf et al 1998). However, this would fail to explain major differences seen between S. cerevisiae and S. paradoxus and different Saccharomyces strains of the same species (Hsu and Chou 2017). Furthermore, it is unclear which mechanisms may be acting on mtDNA selection associated with temperature variation.…”
Section: Mtdna Influences the Fitness Of Yeast Hybrids In An Environmmentioning
confidence: 99%
See 1 more Smart Citation
“…When dividing between mother cell and bud, mitochondria rely on complex network actions in order to distribute the organelles evenly across the cells [31][32][33]. Replication and partitioning of the mitochondrion is not related to the cell cycle, depending instead on the replication and expression of its own genes and nuclear-encoded proteins [10,34]. For mitochondrial biogenesis, both nuclear and mitochondrially encoded components are required [10].…”
Section: Introductionmentioning
confidence: 99%
“…Replication and partitioning of the mitochondrion is not related to the cell cycle, depending instead on the replication and expression of its own genes and nuclear-encoded proteins [10,34]. For mitochondrial biogenesis, both nuclear and mitochondrially encoded components are required [10]. Since the mitogenome encodes a small subset of proteins, it requires the ones encoded in the nucleus in order to express its genome [35].…”
Section: Introductionmentioning
confidence: 99%